Robert B. Parker's Ironhorse - Knott, Robert 1954-; Parker, Robert B. 1932-2010.; Welliver, Titus (New York : Random House Audio, 2013)
Continues the adventures of characters created by the late Robert B. Parker and finds Territorial Marshalls Virgil Cole and Everett Hitch escorting a group of Mexican prisoners on a train trip to the border, only to find the journey complicated by the Governor of Texas and a vengeful outlaw from Virgil's past.
Unabridged.
Compact discs.
Read by Titus Welliver.
Keywords: Cole, Virgil (Fictional character) -- Fiction; Hitch, Everett (Fictional character) -- Fiction; Western stories; Audiobooks